DOCUMENTING COEXISTENCE: A STUDY OF ENVIRONMENTAL NARRATIVES IN DOCUMENTARY FILMS THE ELEPHANT WHISPERERS AND ALL THAT BREATHES - Priya, Tannu; Kusuma, Krishna Sankar; Paul , Pragati (ShodhKosh: Journal of Visual and Performing Arts, 2026)
The Study explores the growing importance of environmental documentaries in fostering dialogue, influencing public consciousness, and documenting the fragile threads of coexistence in an age of ecological uncertainty. The research examines environmental narratives embedded in two critically acclaimed Indian documentary films, The Elephant Whisperers (2022) directed by Kartiki Gonsalves and All That Breathes (2022) directed by Shaunak Sen. Set against the backdrop of India’s rapidly evolving ecological and socio-political landscape, the study investigates how these documentaries depict the complex relationship between humans and non-human life forms, and how they reflect broader environmental concerns such as climate change, species adaptation, coexistence, habitat loss, and human-wildlife conflict. Using a qualitative methodology that includes thematic film analysis, interviews with audiences, and an interview with director Shaunak Sen along with some other documentary filmmakers, the research examines the affective strategies used to portray environmental realities. Audience responses reinforce the impact of these films in raising awareness, evoking empathy, and challenging conventional perceptions of environmental crises. By situating these films within the larger discourse of environmental communication and media ecology, the study argues that through the portrayal of human-wildlife relationships, documentaries play a crucial role in showcasing various environmental issues.